The microbiome and its impact on food allergy and atopic dermatitis in children - Łoś-Rychalska, Ewa; Gołębiewski, Marcin; Grzybowski, Tomasz; Rogalla-Ładniak, Urszula; Krogulska, Aneta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Food allergy (FA) affects 4–10% of children, especially children with atopic dermatitis (AD). During infancy the gut microbiome may determine both the course of FA and tolerance to food allergens. Analogically, the skin microbiome changes in the course of AD. Most studies have associated FA with a lower abundance and diversity of Lactobacillales and Clostridiales, but greater numbers of Enterobacterales, while AD in children has been associated with lower numbers of Staphylococcus epidermidis and S. hominis but an abundance of S. aureus and Streptococcus species. An understanding of the impact of the microbiome on the clinical course of FA and AD may allow for the development of new models of allergy treatment and prevention.